The effect of a low-level yellow laser on improving the stability of stored whole blood - Safa Hassan Mohamed; Mustafa Salih. Al Musawi; Bassam Al-Gailani (Journal of the Pakistan Medical Association, 2024)
Objective: To explore if low-level laser 589nm may stabilise stored whole blood and red blood cell suspension in vitro. Method: The interventional study was conducted from November 2021 to April 2022 at the Postgraduate Medical Physics Laboratory, Mustansiriyah University, Baghdad, Iraq, and comprised blood samples from healthy adults. The samples were obtained put in tubes containing anticoagulant citrate-phosphate dextrose-adenine. Each sample was divided into eight equal aliquots and stored for 21 days at 4ºC. Of the 8 aliquots, 4 were takebn as controls, while the other 4 were irradiated by 589nm laser beam with a radiation dose of 50J/cm² for 15min. Stability test measured by the percentage of haemolysis of an overnight stored red bllod cell in saline solution was done on days 0, 7, 14 and 21 for non-irradiated and radiated aliquots. Data was analysed using SPSS 24. Results: Eight subjects (4 males and 4 females) were included, with mean age 21±3 years (range: 19-24 years). Whole blood samples showed a significant reduction in haemolysis by 40%, 20% and 42% compared to the control samples at days 0, 7 and 14, respectively (p<0.05). Red blood cell suspension showed a significant reduction in haemolysis by 9% compared to the control samples only at day 21 (p<0.05). Conclusion: Low-level laser 589nm beam at 50J/cm² radiation dose was more effective on the stability of stored whole blood than the red blood cell suspension. Key Words: Saline, Hemolysis, Erythrocytes, Adenine, Anticoagulants, Citrates, Glucose, Phosphates, Radiation, Lasers